PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADA KEPUASAN PELANGGAN PADA BENGKEL PT. MAHLIGAI PUTERI BERLIAN (MITSUBISHI)-GARDUJATI BANDUNG - Sjamsuridjal, Sjamsuridjal; Awit Apriliyani (JURNAL BISNIS dan TEKNOLOGI, 2022)
The research was conducted on the customers of the PT. Mahligai Puteri Berlian (Mitsubishi) - Gardujati Bandung. This study aims to determine the effect of service quality and facilities on customer satisfaction. The method used is descriptive associative. The unit of analysis of this research is the individual customer of the workshop. The results showed that there was a partial influence, namely the influence of service quality on customer satisfaction, and the influence of facilities on customer satisfaction, as well as the simultaneous influence of service quality and facilities on customer satisfaction. The implication of this research is that it is hoped that improvements can be made to the services and facilities at the workshop.